A Review on the Impacts of Social Media (International Journal of Innovative Research in Engineering & Management, 2021)
Social networking as a console for people all over the world to  share their personal concerns and ideas in public. Is it necessary  for social media professionals to already grasp what it means  when they comprehend all elements of social media? Ideas,  pictures, movies, and much more are created, shared, and traded  over the internet and in virtual communities, and social networks  have been used to describe the connection between groups of  individuals. Children grow up surrounded by mobile devices and  websites such as Twitter, Myspace, and Facebook, which has  made social media a major part of their life. The social network  alters young people's behavior and how they utilize technology  in their interactions with their parents. Social networking has  two distinct effects. On the plus side, social media may be a  useful tool for professionals. This is accomplished through  assisting young people in marketing their skills and looking for  business opportunities. Social networking platforms may be  effectively used for networking. On the bad side of the internet,  there is a range of risks associated with online communities.  This article discusses the positive and negative effects of social  media in general. The focus is on health, business, education,  society, and youth.
Keywords: Business; Health; Networking Sites; People; Social Media; Society